Peran Pojok Baca Anggrek Bulan dalam Menjadikan Padang Panjang sebagai Kota Literasi - Sri Wahyuni (Media Pustakawan, 2023)
Reading corner is a means of education related to lifelong learning. It's aimed at improving the quality of education in the community. Reading Corner Bank Sampah Anggrek Bulan is one of the TBMs that is active in developing the capabilities of the community by processing garbage into useful objects. This research aims to describe the contribution of the Anggrek Bulan Reading Corner to improving public to support the mission of Padang Panjang City as a City of Literature. The research method used is qualitative, the type of field research, whereas the analysis approach used is descriptive-qualitative. Sampling technique using purposive sampling. As for the informants in this study, they are the founder of the reading corner, the administrator, and the visitor to the reading corner. Data collection through direct field observations, semi-structured interviews, and documentation. Data analysis is done by means of data collection, data reduction, data presentation, and conclusion drawings. The results of this study show that Anggrek Bulan Reading Corner  develops the literacy of the community with a variety of routine activities such as tahfiz, disposing of wastes, and whistling. Its efforts to preserve and promote local wisdom culture are carried out by providing a collection of fiction related to the culture of independence, organizing local cultural activities and inviting experts in the process of transferring information for the young generation to know the culture, in particular Minangkabau culture. These activities have had a significant influence in supporting the Padang Panjang as a City of Literature.